Analyzing the Impact of Macroeconomic Conditions on Third-Party Funds at Bank BCA: A Comprehensive Empirical Study - Sari, Sherly; Fisabilillah, Ladi Wajuba Perdini (Journal of Regional Economics Indonesia, 2025)
This study aims to investigate the impact of macroeconomic conditions on third-party funds at Bank BCA. The independent variables analyzed include inflation, the US Dollar exchange rate, and interest rates, while the dependent variable is the third-party funds from 2016 to 2021. Employing multiple linear regression analysis through EViews 9, the findings reveal that the independent variables collectively exert a significant influence on third-party funds at Bank BCA. Specifically, inflation demonstrates a negative correlation with third-party funds, indicating that rising inflation adversely affects deposit levels. Conversely, the US Dollar exchange rate shows a positive relationship, suggesting that a stronger dollar enhances third-party fund accumulation. Additionally, interest rates negatively impact third-party funds, highlighting the sensitivity of depositors to changes in interest rates. These results underscore the importance of macroeconomic stability in fostering a conducive environment for bank deposits, particularly in the context of Bank BCA.